Preparation method and application of surface defect-rich catalyst for NH3 catalytic oxidation
Through heteropolyacid modified molecular sieve and high-temperature reduction treatment, a surface-rich NH3 catalytic oxidation catalyst was constructed, which solved the problems of low N2 selectivity and insufficient low-temperature activity of existing catalysts under a wide temperature window, and achieved efficient NH3 catalytic oxidation and N2 selectivity improvement.
Patent Information
- Application Number
- CN202311223359.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
The existing NH3 catalytic oxidation catalysts have low N2 selectivity under a wide temperature window and insufficient low-temperature catalytic activity, making it difficult to efficiently remove indoor air pollutants such as NH3.
The molecular sieve was modified by heteropolyacid, and the supported catalyst was reduced at high temperature in a mixed CO reduction atmosphere to construct defect-rich sites on the surface to improve the NH3 catalytic oxidation activity and N2 selectivity of the catalyst.
It is achieved to improve the NH3 conversion rate and N2 selectivity under a wide temperature window, improve the low-temperature activity of the catalyst, and overcome the problems of low low-temperature activity and poor selectivity of the existing catalysts at high-temperature N2.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of NH3 catalytic oxidation catalysts, and in particular relates to a preparation method and application of a surface defect-rich catalyst for NH3 catalytic oxidation. Background Art
[0002] Ammonia is one of the typical air pollutants. At present, the commonly used NH3 treatment technologies include adsorption, absorption, biological decomposition, catalytic decomposition, photocatalytic oxidation and ammonia selective catalytic oxidation (NH3-SCO).
[0003] NH3-SCO technology can directly convert NH3 into N2 and H2O through catalysts. It is easy to operate, has a high NH3 removal rate, and is an efficient and potential ammonia treatment technology; however, the ammonia oxidation process not only produces N2, but also may produce NO, NO2 and N2O that are polluting to the environment. Therefore, only NH3-SCO catalysts with high NH3 conversion rate and N2 selectivity in a wide temperature window can completely convert the escaped NH3 into harmless nitrogen.
[0004] Existing NH3 oxidation catalysts are mainly divided into precious metal catalysts, transition metal and composite oxide catalysts. Most precious metal catalysts show excellent NH3 catalytic activity, but poor N2 selectivity, easy to catalyze the production of NOx and N2O, causing secondary pollution, and expensive. The low-temperature catalytic activity of transition metal catalysts still needs to be improved. Although the special structure can produce synergistic effects at the interface and improve the NH3 oxidation activity, it is difficult to achieve in the actual scale-up production process.
[0005] Patent document CN 110433822A discloses a Co-Mn catalyst for NH3 catalytic oxidation, a preparation method and its application; the invention uses ammonia water as a precipitant, and then obtains a Co-Mn spinel structure catalyst by step-by-step precipitation, and then forms defects by soaking in tetrabutylammonium hydroxide, and the surface of WO3 is modified. The WO3-CoMn2O4 catalyst exhibits good NH3 catalytic performance and N2 selectivity, and the WO3-CoMn2O4 catalyst can achieve 100% NH3 conversion rate at 200°C. However, the catalyst prepared in this patent has low N2 selectivity in the process of NH3 catalytic oxidation.
[0006] Patent document CN 115245823A discloses a defective mixed crystal TiO2 catalyst and its preparation method and application; the invention obtains mixed crystal TiO2 with a specific ratio of anatase and rutile by high-temperature calcination and controlling the calcination conditions; the mixed crystal TiO2 catalyst is beneficial to the catalytic oxidation of HCHO and / or CO and / or NH3, so as to achieve the purpose of simultaneously and efficiently removing multiple indoor air pollutants such as HCHO, CO and NH3; however, the reducing atmosphere used in the patent is a mixture of hydrogen and nitrogen, the explosion concentration range of hydrogen is relatively wide, the risk factor is relatively high, and the catalyst scale-up production process is limited.
[0007] In view of this, continuing to study catalytic oxidation catalysts that can efficiently remove various indoor air pollutants such as HCHO, CO and NH3 becomes a worthy research direction. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a surface defect-rich catalyst for NH3 catalytic oxidation and its application in view of the problems existing in existing NH3 catalytic oxidation catalysts; the preparation method comprises modifying the molecular sieve with a heteropoly acid and performing a high-temperature reduction treatment on the supported catalyst in a mixed reducing atmosphere containing CO, thereby constructing abundant defect sites on the catalyst surface, thereby facilitating the NH3 catalytic oxidation activity of the catalyst in a wide temperature window and improving the N2 selectivity at the same time.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] In a first aspect, a method for preparing a surface defect-rich catalyst for catalytic oxidation of NH3 is provided, comprising the following steps:
[0011] (1) Preparation of catalyst carrier
[0012] The heteropoly acid is mixed with molecular sieve and deionized water to obtain a mixture, and the mixture is ground (placed in a ball mill, for example, the mixture to be ground is placed in a zirconia ball mill jar, and a certain amount of zirconia grinding balls are added); the wet powder obtained by grinding is vacuum dried, and the dried mixture is calcined under an inert atmosphere to obtain a catalyst carrier powder;
[0013] (2) Preparation of Catalyst
[0014] Weigh a manganese precursor salt and an auxiliary agent precursor salt and dissolve them in water to prepare an aqueous solution containing the manganese precursor salt and the auxiliary agent precursor salt; then add the catalyst carrier prepared in step (1) to the aqueous solution containing the manganese precursor salt and the auxiliary agent precursor salt (for example, by one or more methods selected from the group consisting of an impregnation method, a coprecipitation method, and a citric acid method) to load the manganese precursor salt and the auxiliary agent precursor salt on the catalyst carrier; then vacuum dry the catalyst carrier; and then calcine the dried product under an inert atmosphere to obtain a supported catalyst containing manganese oxide and auxiliary agent oxide;
[0015] (3) Catalyst reduction
[0016] The supported catalyst obtained in step (2) is placed in a mixed reducing atmosphere containing CO / inert gas for reduction to obtain a catalyst with rich surface defects.
[0017] According to the preparation method provided by the present invention, in some embodiments, in step (1), the mass ratio of molecular sieve: heteropolyacid: deionized water is 1:(0.005-0.02):(1.5-3), for example, 1:0.006:2, 1:0.008:2, 1:0.01:2, 1:0.015:2.5, 1:0.015:3, 1:0.02:3, preferably 1:(0.008-0.015):(2-2.5).
[0018] In some embodiments, the molecular sieve is selected from one or more of Y-type molecular sieve, Beta-type molecular sieve and ZSM series molecular sieve; preferably, Si / Al of the molecular sieve is ≤100 (for example, Si / Al is 30, 50, 60, 80, 100); in the text, the molecular sieve can be, but is not limited to, purchased from Nankai Catalyst Factory.
[0019] In some embodiments, the heteropoly acid is selected from one or more of phosphomolybdic acid, phosphotungstic acid and silicotungstic acid.
[0020] In some embodiments, in step (1), the mass ratio of the mixture to be ground to the grinding porcelain balls is (1-5):1, for example, 1.5:1, 2.5:1, 3:1, 3.5:1, 4.5:1, preferably (2-4):1.
[0021] In some embodiments, the grinding process conditions include: a grinding speed of 300-500 r / min (e.g., 320 r / min, 400 r / min, 480 r / min), preferably 350-450 r / min; a grinding time of 20-50 min (e.g., 25 min, 35 min, 45 min), preferably 30-40 min.
[0022] In some embodiments, in step (1), the process conditions of vacuum drying include: time of 12-24h (e.g., 15h, 18h, 20h), temperature of 60-80°C (e.g., 65°C, 70°C, 75°C), and vacuum degree of ≤50Pa (e.g., 1Pa, 5Pa, 10Pa, 20Pa, 30Pa, 40Pa).
[0023] In some embodiments, in step (1), the calcination process conditions include: using programmed temperature rise, heating at room temperature to 200°C at a heating rate of 5°C / min and maintaining for 1-2h (e.g., 1.5h), heating at 200°C to 350°C at a heating rate of 5°C / min and maintaining for 0.5-2h (e.g., 1h, 1.5h), heating at 350°C to 500°C at a heating rate of 10°C / min and maintaining for 1-2h (e.g., 1.5h). During the calcination process, the inert atmosphere can be, for example, a nitrogen atmosphere.
[0024] In some embodiments, in step (1), the specific surface area of the catalyst carrier is ≥ 400 m 2 / g, for example, 420m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g.
[0025] According to the preparation method provided by the present invention, in some embodiments, in step (2), the manganese precursor salt is a water-soluble precursor salt of manganese, selected from one or more of manganese acetate, manganese nitrate and manganese sulfate.
[0026] In the catalyst of the present invention, the auxiliary element is one or two of Co, Fe, Ni, Cu, and Zn. In some embodiments, the auxiliary precursor salt is a water-soluble precursor salt of the auxiliary element, selected from one or more of cobalt nitrate, cobalt chloride, ferric acetate, ferric oxalate, ferric nitrate, ferric chloride, ferric sulfate, nickel nitrate, nickel chloride, nickel sulfate, copper nitrate, copper sulfate, copper acetate, copper oxalate, zinc acetate, zinc chloride, and zinc nitrate.
[0027] In step (2), the catalyst support is added to an aqueous solution containing a manganese precursor salt and an additive precursor salt, and the active component can be loaded on the support by one or more methods of impregnation, coprecipitation, and citric acid method. The process conditions of the impregnation method, coprecipitation method, and citric acid method are conventional operations in the art and will not be described here.
[0028] In some embodiments, in step (2), the process conditions of vacuum drying include: temperature of 60-80°C (e.g., 65°C, 70°C, 75°C), time of 12-24h (e.g., 15h, 18h, 20h), vacuum degree of ≤50Pa (e.g., 1Pa, 5Pa, 10Pa, 20Pa, 30Pa, 40Pa, 45Pa), preferably ≤30Pa.
[0029] In some embodiments, in step (2), the calcination process conditions include: calcination temperature of 400-550° C. (e.g., 420° C., 480° C., 520° C.), preferably 450-500° C.; calcination time of 3-6 h (e.g., 3.5 h, 4.5 h, 5.5 h), preferably 4-5 h. During the calcination process, the inert atmosphere may be, for example, a nitrogen atmosphere.
[0030] In some embodiments, in step (2), the loading amount of the manganese oxide is 1-8wt% (for example, 2wt%, 4wt%, 5wt%, 7wt%), preferably 3-6wt% of the total mass of the supported catalyst; the loading amount of the promoter oxide is 0.5-5wt% (for example, 0.8wt%, 1.2wt%, 1.5wt%, 2wt%, 2.5wt%, 3.5wt%, 4wt%, 4.5wt%) of the total mass of the supported catalyst, preferably 1-3wt%.
[0031] In some embodiments, in step (3), the inert gas is selected from one or more of nitrogen, helium and argon.
[0032] In some embodiments, in step (3), the total flow rate of the mixed reducing atmosphere is 90 to 240 L / h·g -1 Catalyst (e.g., 100 L / h·g -1 Catalyst, 150L / h·g -1 Catalyst, 200L / h·g -1 Catalyst, 220L / h·g -1 Catalyst), preferably 120 to 180 L / h·g -1 Catalyst; wherein the amount of CO added accounts for 0.1 to 6 vol% (e.g., 0.5 vol%, 1 vol%, 2.5 vol%, 3 vol%, 4 vol%, 5.5 vol%) of the total volume of the mixed reducing atmosphere, preferably 2 to 5 vol%.
[0033] In some embodiments, in step (3), the reduction process conditions include: the reduction temperature is 450-600°C (for example, 480°C, 520°C, 580°C), preferably 500-550°C; the reduction time is 6-24h (for example, 8h, 12h, 15h, 22h), preferably 10-20h.
[0034] In the second aspect, a surface defect-rich catalyst prepared by the preparation method described above is provided for use in NH3 catalytic oxidation reaction. Herein, the process steps and process conditions of NH3 catalytic oxidation reaction are conventionally selected in the art and will not be described in detail here.
[0035] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0036] (1) The present invention uses molecular sieve (with a certain Si / Al ratio) as a precursor, dopes a certain amount of heteropoly acid, and uses mechanical ball milling to put the molecular sieve and heteropoly acid particles in a high-energy unstable state through mechanical force, fully fuses, reduces the particle size, creates internal lattice defects or distortions, increases the specific surface area and surface acidity of the carrier, can promote the formation of defect sites on the carrier to a certain extent, and further promote the adsorption and oxidation activation of NH3, while improving the N2 selectivity;
[0037] (2) At the same time, the present invention can construct abundant defect sites on the catalyst surface by subjecting the prepared supported catalyst to high-temperature reduction treatment in a mixed atmosphere containing CO / inert gas of a certain concentration, thereby promoting oxygen conduction and electron transfer of the catalyst, thereby improving the low-temperature activity of the catalyst;
[0038] The catalyst prepared by the preparation method of the present invention is used for the catalytic oxidation reaction of NH3, and can simultaneously improve the NH3 conversion rate and N2 selectivity in a wide temperature window. DETAILED DESCRIPTION
[0039] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.
[0040] <Source of raw materials>
[0041] USY molecular sieve, purchased from commercial sources;
[0042] Phosphomolybdic acid, purchased from commercial sources;
[0043] Manganese nitrate, commercially available;
[0044] Ferric nitrate was purchased from commercial sources.
[0045] Example 1
[0046] (1) Preparation of catalyst carrier
[0047] 50 g of USY molecular sieve (Si / Al is 60) was added to a beaker, and then phosphomolybdic acid and deionized water were added and mixed, and the addition amount was adjusted so that the mass ratio of molecular sieve: heteropoly acid: deionized water was 1:0.01:2, and the whole mixture was placed in a zirconia ball mill after stirring with a glass rod, and then 35 g of zirconia grinding porcelain balls were added, and the mixture was ground at a grinding speed of 400 r / min for 30 min;
[0048] The wet powder obtained after grinding was vacuum dried for 24 hours (drying temperature was 70°C, drying time was 20 hours, vacuum degree was 30Pa); the dried powder was placed in a tubular furnace under a nitrogen atmosphere for high-temperature calcination, and the calcination temperature program was as follows: heating to 200°C at a heating rate of 5°C / min at room temperature and kept at this temperature for 2 hours, heating to 350°C at a heating rate of 5°C / min at 200°C and kept at this temperature for 1 hour, heating to 500°C at a heating rate of 10°C / min at 350°C and kept at this temperature for 2 hours; the specific surface area was 506m 2 / g of catalyst carrier;
[0049] (2) Preparation of Catalyst
[0050] Manganese nitrate is used as a manganese precursor salt and ferric nitrate is used as an auxiliary iron precursor salt, and they are dissolved in water to prepare an aqueous solution; then the catalyst carrier prepared in step (1) is placed in the aqueous solution of the manganese nitrate precursor salt and the aqueous solution of the auxiliary iron nitrate precursor salt, and manganese nitrate and auxiliary iron nitrate are loaded on the catalyst carrier by an impregnation method, wherein the impregnation temperature is 70° C. and the impregnation time is 8 hours;
[0051] The wet catalyst powder after impregnation is then placed at 80°C for vacuum drying for 20 hours, with a vacuum degree of 10Pa; the dried powder is placed in a tube furnace for high-temperature calcination, wherein the calcination temperature is 450°C and the calcination time is 4 hours; after calcination, a supported catalyst is obtained, wherein the loading amount of manganese oxide accounts for 5wt% of the total mass of the supported catalyst, and the loading amount of iron oxide accounts for 3wt% of the total mass of the supported catalyst;
[0052] (3) Catalyst reduction
[0053] Weigh 5 g of the supported catalyst prepared in step (2) and place it in a mixed reducing atmosphere of CO / nitrogen for high temperature reduction. The total flow rate of the mixed reducing atmosphere is 180 L / h·g -1 The catalyst comprises: the amount of CO added is 5 vol% of the total volume of the mixed reducing atmosphere; the reduction temperature is 550°C; and the reduction time is 18 hours; after high-temperature reduction, a catalyst with rich surface defects is obtained.
[0054] Example 2
[0055] The preparation method of the catalyst with rich surface defects is as follows:
[0056] In step (1), the mass ratio of pseudo-boehmite: heteropoly acid: deionized water is 1:0.005:2, and the other process conditions are the same as those in Example 1; the specific surface area of the obtained catalyst carrier is 520m 2 / g;
[0057] Step (2) is the same as in Example 1;
[0058] Step (3) is the same as in Example 1.
[0059] Example 3
[0060] The preparation method of the catalyst with rich surface defects is as follows:
[0061] In step (1), the mass ratio of pseudo-boehmite: heteropoly acid: deionized water is 1:0.02:3, and the other process conditions are the same as those in Example 1; the specific surface area of the obtained catalyst carrier is 450m 2 / g;
[0062] Step (2) is the same as in Example 1;
[0063] Step (3) is the same as in Example 1.
[0064] Example 4
[0065] The preparation method of the catalyst with rich surface defects is as follows:
[0066] In step (2), the amount of manganese nitrate and iron nitrate added is changed so that the loading amount of manganese oxide accounts for 3 wt% of the total mass of the supported catalyst and the loading amount of iron oxide accounts for 1 wt% of the total mass of the supported catalyst;
[0067] Step (1) is the same as in Example 1;
[0068] Step (3) is the same as in Example 1.
[0069] Example 5
[0070] The preparation method of the catalyst with rich surface defects is as follows:
[0071] In step (2), the amount of manganese nitrate and iron nitrate added is changed so that the loading amount of manganese oxide accounts for 8 wt% of the total mass of the supported catalyst and the loading amount of iron oxide accounts for 3 wt% of the total mass of the supported catalyst;
[0072] Step (1) is the same as in Example 1;
[0073] Step (3) is the same as in Example 1.
[0074] Example 6
[0075] The preparation method of the catalyst with rich surface defects is as follows:
[0076] In step (3), the total flow rate of the mixed reducing atmosphere is 120 L / h·g -1 Catalyst, CO added in an amount of 2 vol% of the total volume of the mixed reducing atmosphere;
[0077] Step (1) is the same as in Example 1;
[0078] Step (2) is the same as in Example 1.
[0079] Example 7
[0080] The preparation method of the catalyst with rich surface defects is as follows:
[0081] In step (3), the total flow rate of the mixed reducing atmosphere is 240 L / h·g -1 Catalyst, CO accounts for 6 vol% of the total volume of the mixed reducing atmosphere; the reduction temperature is 500°C, and the reduction time is 10 h;
[0082] Step (1) is the same as in Example 1;
[0083] Step (2) is the same as in Example 1.
[0084] Comparative Example 1
[0085] The preparation method of the catalyst for catalytic oxidation of NH3 refers to Example 1, except that step (3) is not performed, that is, the prepared supported catalyst is not placed in a mixed reducing atmosphere containing CO / inert gas for high-temperature reduction.
[0086] Comparative Example 2
[0087] (1) Preparation of catalyst
[0088] Manganese nitrate is used as a manganese precursor salt and ferric nitrate is used as an auxiliary iron precursor salt, and they are dissolved in water to prepare an aqueous solution; then a commercially available unmodified USY molecular sieve (Si / Al is 60) is directly placed as a catalyst carrier in the aqueous solution of the manganese nitrate precursor salt and the aqueous solution of the auxiliary iron nitrate precursor salt, and manganese nitrate and auxiliary iron nitrate are loaded on the catalyst carrier by an impregnation method, wherein the impregnation temperature is 70° C. and the impregnation time is 8 hours;
[0089] The wet catalyst powder after impregnation is then placed at 80°C for vacuum drying for 20 hours, with a vacuum degree of 10Pa; the dried powder is placed in a tube furnace for high-temperature calcination, wherein the calcination temperature is 450°C and the calcination time is 4 hours; after calcination, a supported catalyst is obtained, wherein the loading amount of manganese oxide accounts for 5wt% of the total mass of the supported catalyst, and the loading amount of iron oxide accounts for 3wt% of the total mass of the supported catalyst;
[0090] (2) Catalyst reduction
[0091] Weigh 5 g of the supported catalyst prepared in step (2) and place it in a mixed reducing atmosphere of CO / nitrogen for high temperature reduction. The total flow rate of the mixed reducing atmosphere is 180 L / h·g -1 The catalyst comprises: the amount of CO added is 5 vol% of the total volume of the mixed reducing atmosphere; the reduction temperature is 550°C; and the reduction time is 18 hours; after high-temperature reduction, a catalyst with rich surface defects is obtained.
[0092] Performance test of the catalysts prepared in each embodiment and comparative example:
[0093] An experimental platform was built, and the catalysts prepared in the above embodiments and comparative examples were selected and placed in a stainless steel fixed bed reactor. After stabilization for 2 h in the temperature range of 200-420 ° C, the NH3 catalytic conversion efficiency at each selected temperature point was tested. Simulated flue gas (NH3 = 500 ppm, O2 = 3%, H2O = 10%, and the rest was N2 as the balance gas) was introduced, and the space velocity = 150000 h -1 ; The concentrations of NH3, NO, NO2, and N2O at the catalyst inlet and outlet were tested using a FTIR Fourier transform infrared flue gas analyzer (MKS, Multigas 6030), and the conversion rate of NH3 and the selectivity of N2 were calculated accordingly.
[0094]
[0095]
[0096] The catalytic performance test results of the catalysts prepared in various embodiments and comparative examples are shown in Table 1.
[0097] Table 1 Catalytic performance test results of each catalyst
[0098]
[0099] It can be seen from the experimental results of Table 1 that the present invention, by modifying the molecular sieve carrier with high specific surface area by heteropoly acid, and loading a specific content of active components, and obtaining a NH3 catalytic oxidation catalyst with rich defect sites on the surface through high-temperature reduction in an inert atmosphere, overcomes the problem of low NH3 catalytic oxidation activity at low temperature and poor N2 selectivity at high temperature, improves the low-temperature activity of the catalyst, and then promotes the adsorption and oxidation activation of NH3, while improving the N2 selectivity. Compared with Comparative Example 1, in the method of each embodiment, after high-temperature reduction in an inert atmosphere, the NH3 conversion rate under the wide temperature window of the catalyst is significantly improved, and the N2 selectivity is also improved to varying degrees. Compared with Comparative Example 2, the catalyst prepared by the carrier of each embodiment after being modified by heteropoly acid has higher NH3 catalytic activity and N2 selectivity. By comparison, it can be found that the amount of heteropoly acid is not more conducive to improving the NH3 catalytic activity, because if the amount of heteropoly acid is not within the appropriate range, the high-speed mechanical mixing of heteropoly acid will occupy the pores of the molecular sieve, reduce the specific surface area of the carrier, and affect the adsorption of NH3 by the catalyst.
[0100] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a surface defect-rich catalyst for catalytic oxidation of NH3, characterized in that: The following steps are involved: (1) Preparation of catalyst carrier The heteropoly acid is mixed with molecular sieve and deionized water to obtain a mixture, and the mixture is ground; the wet powder obtained by grinding is vacuum dried, and the dried mixture is placed in an inert atmosphere for calcination to obtain a catalyst carrier powder; (2) Preparation of Catalyst Weighing a manganese precursor salt and an auxiliary agent precursor salt and dissolving them in water to prepare an aqueous solution containing the manganese precursor salt and the auxiliary agent precursor salt; Then, the catalyst carrier prepared in step (1) is added into an aqueous solution containing a manganese precursor salt and an auxiliary agent precursor salt, so that the manganese precursor salt and the auxiliary agent precursor salt are loaded on the catalyst carrier; Then, the product is dried in vacuum; and the dried product is calcined under an inert atmosphere to obtain a supported catalyst containing manganese oxide and promoter oxide; (3) Catalyst reduction The supported catalyst obtained in step (2) is placed in a mixed reducing atmosphere containing CO / inert gas for reduction to obtain a catalyst with rich surface defects.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of molecular sieve: heteropoly acid: deionized water is 1: (0.005-0.02): (1.5-3), preferably 1: (0.008-0.015): (2-2.5); The molecular sieve is selected from one or more of Y-type molecular sieve, Beta-type molecular sieve and ZSM series molecular sieve; preferably, Si / Al of the molecular sieve is ≤100; The heteropoly acid is selected from one or more of phosphomolybdic acid, phosphotungstic acid and silicotungstic acid.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the mixture to be ground to the grinding porcelain balls is (1-5):1, preferably (2-4):1; The grinding process conditions include: a grinding speed of 300-500 r / min, preferably 350-450 r / min; and a grinding time of 20-50 min, preferably 30-40 min.
4. The preparation method according to claim 1, characterized in that: In step (1), the process conditions of vacuum drying include: time of 12-24h, temperature of 60-80°C, vacuum degree of ≤50Pa; and / or The calcination process conditions include: heating to 200°C at a heating rate of 5°C / min at room temperature and maintaining for 1-2 hours, heating to 350°C at a heating rate of 5°C / min at 200°C and maintaining for 0.5-2 hours, and heating to 500°C at a heating rate of 10°C / min at 350°C and maintaining for 1-2 hours.
5. The preparation method according to claim 1, characterized in that: In step (1), the specific surface area of the catalyst carrier is ≥400m 2 / g.
6. The preparation method according to claim 1, characterized in that: In step (2), the manganese precursor salt is selected from one or more of manganese acetate, manganese nitrate and manganese sulfate; The auxiliary agent precursor salt is selected from one or more of cobalt nitrate, cobalt chloride, ferric acetate, ferric oxalate, ferric nitrate, ferric chloride, ferric sulfate, nickel nitrate, nickel chloride, nickel sulfate, copper nitrate, copper sulfate, copper acetate, copper oxalate, zinc acetate, zinc chloride and zinc nitrate.
7. The preparation method according to claim 1, characterized in that: In step (2), the process conditions of vacuum drying include: temperature of 60-80°C, time of 12-24h, vacuum degree of ≤50Pa, preferably ≤30Pa; The calcination process conditions include: calcination temperature of 400-550° C., preferably 450-500° C.; calcination time of 3-6 hours, preferably 4-5 hours.
8. The preparation method according to claim 1, characterized in that: In step (2), the loading amount of the manganese oxide accounts for 1-8wt% of the total mass of the supported catalyst, preferably 3-6wt%; the loading amount of the promoter oxide accounts for 0.5-5wt% of the total mass of the supported catalyst, preferably 1-3wt%.
9. The preparation method according to claim 1, characterized in that: In step (3), the inert gas is selected from one or more of nitrogen, helium and argon; The total flow rate of the mixed reducing atmosphere is 90 to 240 L / h·g -1 Catalyst, preferably 120 to 180 L / h·g -1 Catalyst; wherein the amount of CO added accounts for 0.1 to 6 vol%, preferably 2 to 5 vol% of the total volume of the mixed reducing atmosphere; The reduction process conditions include: reduction temperature of 450-600° C., preferably 500-550° C.; reduction time of 6-24 h, preferably 10-20 h.
10. Use of the surface defect-rich catalyst prepared by the preparation method according to any one of claims 1 to 9 in catalytic oxidation reaction of NH3.
Citation Information
Patent Citations
Co-Mn catalyst for catalytic oxidation of NH3, preparation method and applications thereof
CN110433822A
Defected mixed crystal type TiO2 catalyst as well as preparation method and application thereof
CN115245823A
analogical process FOR THE PREPARATION OF THERAPEUTICALLY ACTIVE Z-N,N-DIMETHYL-3-(4-BROMPHENYL)-3-(3-PYRIDYL)-ALLYLAMINE DIHYDROCHLORIDE MONOHYDRATE.
NO150000B
Cited By
Environment-friendly sulfide removal agent for oil and gas fields
CN120399741A